Investigation of coherent acoustic phonons in THz quantum cascade laser structures - Hettich, M; Bruchhausen, A; Lloyd-Hughes, J; Gebs, R; Bartels, A; Fischer, M; Beck, M; Scalari, G; Faist, J; Dekorsy, T (2011)
Coherent zone folded acoustic phonons in terahertz quantum cascade laser (QCL) structures [1] are investigated by high-speed asynchronous optical sampling [2]. This method is based on two Ti:sapphire lasers with repetition rates of 1 GHz respectively. The time delay between pump and probe pulse is achieved by an offset in repetition rate of 5kHz. This allows for fast scanning times without moving mechanical parts [3]. © 2011 IEEE.